A Framing Analysis of News Coverage of Book Seizure Following The “17+8 People’s Demands” Demonstration on Tempo.co and CNNIndonesia.com - Dewi Putri Yanti; Khaerudin Imawan (Jurnal Bisnis dan Komunikasi Digital, 2026)
The seizure of books belonging to demonstrators following the “17+8 People’s Demands” protest in August 2025 sparked controversy in the public sphere. The books confiscated by authorities were considered part of the evidence of the riots, yet they were also viewed as symbols of freedom of thought and literacy. This incident has sparked a debate regarding the boundary between law enforcement and the protection of the right to knowledge. Online media play a crucial role in shaping public perception of this issue through varying reporting styles; Tempo.co and CNNIndonesia.com, as national media outlets, exhibit distinct editorial approaches in presenting this event. This study employs a comparative qualitative approach using Robert N. Entman framing analysis model to examine five Tempo.co news articles from September 23, 2025, to October 2, 2025, and five CNNIndonesia.com news articles from September 19 to 27, 2025, supplemented by in-depth interviews with readers. The results indicate that Tempo.co frames the book seizure as an issue of freedom of thought and literacy, whereas CNNIndonesia.com places greater emphasis on legal and security aspects. These framing differences influence how readers understand the event. This study concludes that the media plays a strategic role in shaping public perception regarding issues of freedom of expression and the actions of state authorities within a democratic context.